The Phenomenon of Biodiesel Heating: Its Effect on Viscosity, Density, and Emission - Barokah Barokah; Semin Semin; Beny Cahyono; Bambang Sampurno; Ahmad Ilham Ramadhani; M. Bintang Fikri (International Journal of Marine Engineering Innovation and Research, 2022)
Biodiesel fuel is a mixture of diesel oil mixed with vegetable oil (palm). The composition of the mixture affects its properties, especially viscosity and density. The research was conducted to determine the effect of increasing temperature on these properties. By applying several experimental methods, including the ASTM D 445-95 method, the pycnometer method, and the particulate emission test method. The biodiesel test was carried out with variations in temperature of 30oC, 40oC, 50oC, 60oC, and 70oC at room conditions of 24.0oC temperature and 71% humidity. From the temperature variation, the viscosity is 2.23 cSt, 2.61 cSt, 3.1 cSt, 3.7 cSt, and 4.45 cSt. The results of the research prove that the increase in biodiesel temperature affects decreasing viscosity and density which has an impact on reducing particulate emissions.